Diagnosa Penyakit Gigi Menggunakan Sistem Pakar - Wakhidah, Nur (Jurnal Transformatika, 2004)
Expert System is one of many application computer on Artificial Intelligence, Expert System has 2 part, there are Knowledge Base and Inference Engine. Knowledge Base is a basic of knowledge in database and Inference Engine is engine to make decision support for find the problem and solution. This system can use for diagnose about health of tooth, so computer as expert systems can help the patients to get the solution.